PENDEKATAN KEADILAN RESTORATIF TERHADAP ANAK YANG BERHADAPAN DENGAN HUKUM - Edy Tarsono (Jurnal Hukum dan Bisnis (Selisik), 2022)
The conditions experienced by Indonesian children at this time are not in accordance with the expectations of parents in general. In a number of criminal cases, not least involving children. Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, was formed as one of the efforts to foster and protect in the framework of guaranteeing the physical, mental and social development of children, wholly harmonious and balanced. In Article 69 of the SPPA Law, it is stated that children are only sentenced or subject to action based on the provisions of the criminal justice system for children and children who are not yet 14 (fourteen) years old are only subject to action. what happened then can be used as a basis for the judge’s consideration, not to impose a sentence or take action by considering the aspects of justice and humanity. The problem is in fulfilling restorative justice as a settlement of criminal cases involving perpetrators, victims, families of perpetrators or victims, and other related parties to work together, seek a fair solution by emphasizing restoration of justice to its original state, but punishment which leads to retaliation often occurs in the context of Children Against the Law (ABH). This research was conducted using normative juridical methods. The research approach uses a statutory approach. The data source used in this study is a secondary data source which is then analyzed qualitatively